Empowering Youth to Enhance the Productivity of Hydroponic Horticultural Crops in Sungai Duren Village, Jambi Luar Kota District - Satria, Eko; Lutfiah, Qonita; Azzahra, Sylka; Jamaluddin; Novita, Sri (Jurnal Karya Abdi Masyarakat, 2026)
The younger generation today plays a strategic role in efforts to improve quality in the field of agriculture. Sungai Duren Village is one of the oldest villages in Jambi Province. This village is divided into three hamlets: Tuo Hamlet, Baru Hamlet, and Pasir Raya Hamlet. Looking at the population data, it shows that the farmers in Desa Sungai Duren are predominantly aged between 45-60 years. The potential that can be developed in the village becomes one of the supporting factors for the village innovation program that takes the theme of a young farmer studio with the title "Empowerment of Youth Supporting the Productivity of Horticultural Plants Based on Hydroponics." Therefore, our team has a solution for empowering the youth in Sungai Duren Village, Jambi Luar Kota District, which will focus on increasing the productivity of horticultural plants through hydroponic methods. Hydroponics is a planting technique that does not use soil, but rather uses a nutrient-containing water solution as the growing medium. Therefore, this program aims to involve the younger generation in modern agriculture, enhance skills, and encourage innovation in plant cultivation.